Field investigation on the change process of microbial community structure in large-deep reservoir during the initial impoundment. (15th July 2023) - Liang, Sizhen; Zhang, Fangbo; Li, Ran; Sun, Hailong; Feng, Jingjie; Chen, Zhuo; Lin, Honghui
Abstract: During the initial impoundment of large-deep reservoir, the aquatic environment changed dramatically in various aspects such as water level, hydrological regime, and pollutants, which could alter microorganisms' community structure, break the balance of the aquatic ecosystem and even endanger the aquatic ecosystem. However, the interaction of microbial communities and water environment during the initial impoundment process of a large-deep reservoir remained unclear. To this end, in-situ monitoring and sampling analysis on water quality and microbial communities during the initial impoundment process of a typical large-deep reservoir named Baihetan were conducted so as to explore the response of microbial community structure to the changes of water environmental factors during the initial impoundment of large deep reservoir and reveal the key driving factors affecting microbial community structure. The spatio-temporal variation in water quality was analyzed, and the microbial community structure in the reservoir was investigated based on high-throughput sequencing. The results showed that the COD of each section increased slightly, and the water quality after impoundment was slightly poorer than that before the impoundment. Water temperature and pH were proved to be the key factors affecting the structure of bacterial and eukaryotic communities respectively during the initial impoundment. The research results revealed the role of microorganisms and their interaction with biogeochemical processes in the large-deep reservoir ecosystem, which was crucial for later operation and management of the reservoir and the protection of the reservoir water environment. Graphical abstract: Image 1 Highlights: Water impoundment process affects microbial community variation. In-situ monitoring and sample analysis of water quality and microbial communities. Water temperature is the key factor affecting the bacterial community structure. PH is identified as the key factor affecting the eukaryotic community structure. Stratification of water temperature occurred with a maximum variation of 1.8 °C.